Minimum Wages in New Zealand: Policy and Practice in the 21st Century - David C. Maré; Dean Hyslop (Institute of Labor Economics (IZA), 2021)
New Zealand has seen dramatic changes in minimum wage policies since 2000. The adult minimum wage has increased 75% in CPI-adjusted real terms. In addition, the youth minimum wage was abolished in two stages, resulting in a 125% increase in the real minimum wage for 16–19-year-old workers. We review the motivations for minimum wages and the changes and analyse how they have affected workers outcomes. We find that the minimum wage now strongly determines the wages of teenage workers, with the minimum wage now at the median wage of teenagers, and over half of 16–17-year-olds, and about 40% of 18–19-year-olds, earning at or below the minimum. Although we find no clear evidence that increases in the minimum wage have led to adverse employment effects, we expect there are downside risks for youth and low skilled workers' employment. As minimum wage workers are broadly spread across the household income distribution, we conclude that minimum wages are largely ineffective as a redistributive income support policy.
Keywords: J21; J23; J24; J31; J38; 330; minimum wages; employment; earnings inequality; income inequality